Predictive Value of Decreasing Antithrombin III in Deep-Vein Thrombosis - Andreasen, Thorkild Lund (Thrombosis and Haemostasis, 1980)
Antithrombin III (At-III) was measured at the time of admission and two days later in 131 patients laid up in a coronary care unit. The patients were examined for deep-vein thrombosis (DVT) clinically and by means of 125I-fibrinogen scanning. 19 patients developed DVT. In 11 subjects with and 25 without DVT At-III decreased more than 10%. And in 7 with and 17 without DVT At-III decreased more than 15%. One person with DVT had subnormal At-III. By using decrease of At-III or subnormal initial At-III to predict DVT the following predictive value (PV) were found. Decrease ≤ 10%, PV pos.= 0.32 and PV neg. = 0.93. Decrease ≤ 15%, PV pos. = 0.32 and PV neg. = 0.90. The positive predictive values obtained were too low to let decreasing At-III give occasion for prophylactic anticoagulant treatment.
Keywords: Antithrombin III; Decrease; Deep-vein thrombosis; Predictive values; Myocardial infarction